Energy storage properties of NaNbO3-CaZrO3 ceramics with coexistence of ferroelectric and antiferroelectric phases. Issue 15 (December 2018) - Liu, Zhiyong; Lu, Jinshan; Mao, Yuqing; Ren, Pengrong; Fan, Huiqing
Abstract: Anti-ferroelectric materials with large saturated polarization, small remnant polarization, and moderate breakdown strength are receiving increasing attention for modern high-power electrical systems. Here we demonstrated that by incorporating CaZrO3 into NaNbO3 ceramics, the antiferroelectricity in NaNbO3 -CaZrO3 solid solutions could be stabilized at room temperature. The effects of phase constitution and microstructure on the dielectric properties, electrical breakdown strength, and energy storage properties of the NaNbO3 -CaZrO3 ceramics were investigated. Ferroelectric and antiferroelectric phase coexistence in the NaNbO3-CaZrO3 was confirmed by XRD and TEM analyses. With increasing CaZrO3 content, the grain size was reduced, and the dielectric breakdown strength was improved. Therefore, a high energy density of 0.55 J/cm 3 and efficiency of 63% was obtained in the NaNbO3 -0.04CaZrO3 ceramics. These lead-free NaNbO3 -CaZrO3 antiferroelectrics with good electrical energy storage can be exploited for high-power storage devices.